Effect of Spirulina on antioxidant status and exercise-induced oxidative stress of Indian athletes in comparison to a commercial antioxidant - Kalpana, K.; Kusuma, D. L.; Lal, P. R.; Khanna, G. L. (Asian Journal of Exercise & Sports Science, 2012)
The present study was performed to investigate the effect of spirulina on serum antioxidant status and exercise-induced oxidative stress of athletes in comparison to a commercial antioxidant supplement (CAS). A total of 90 male athletes aged 1521 volunteered for the study and were divided (n = 45) into two groups: (1) aerobic exercise group (AEG) and (2) mixed exercise group (MEG). The exercise groups were further randomly divided into (i) Control Group (CG), (ii) Experimental Group I (EGI), and (iii) Experimental Group II (EGII) with 15 subjects in each group in a double blind fashion. The CG did not receive any supplement. Spirulina (3g/day) for EGI and CAS (1 capsule/day) for EGII were administered for 60 days. During supplementation the control and experimental groups performed the same volume of training and dietary intake. Anthropometric measurements and dietary intake were assessed. A blood test was done to determine the pre- and post-levels of serum ?-carotene, tocopherol, ascorbic acid, and malondialdehyde (MDA). The supplementation of spirulina and CAS resulted in significant increase (p < 0.05) in the levels of serum ?-carotene, serum ?-tocopherol, and plasma ascorbic acid in both AEG and MEG. A significant decrease (p < 0.05) in the level of MDA in the two supplemented groups was also observed. No significant difference was found between spirulina and CAS supplemented groups. Supplementation with spirulina and CAS improves serum antioxidant status and confers protection against exercise-induced oxidative stress.